2017
DOI: 10.1556/004.2017.045
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adrenocortical reserve capacity and inflammatory parameters in critically ill dogs

Abstract: Inflammatory markers and adrenocorticotropic hormone (ACTH) stimulation test results may help us recognise critically ill dogs with poor disease outcome. Systemic inflammatory response syndrome (SIRS) criteria, the fast version of the Acute Patient Physiologic and Laboratory Evaluation Score (APPLE), complete blood count, albumin and C-reactive protein (CRP) levels, baseline and stimulated cortisol levels and Δcortisol value were recorded in 50 client-owned dogs admitted to the Small Animal Hospital of the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Similar results were obtained by studying critically ill human and canine patients, i.e. plasma cortisol level varied in a wide range and mortality was associated with higher cortisol concentrations 46 49 , 55 58 . On the other hand, we could not find a significant relationship between the above-mentioned parameters such as serum CRP level and baseline serum total cortisol level and cGRα and cGR-P mRNA level or ratio of cGRα and cGR-P expression.…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were obtained by studying critically ill human and canine patients, i.e. plasma cortisol level varied in a wide range and mortality was associated with higher cortisol concentrations 46 49 , 55 58 . On the other hand, we could not find a significant relationship between the above-mentioned parameters such as serum CRP level and baseline serum total cortisol level and cGRα and cGR-P mRNA level or ratio of cGRα and cGR-P expression.…”
Section: Discussionsupporting
confidence: 81%
“…These results are likely a response to the stress associated with the underlying disease of whipworm infection with secondary circulatory shock and dehydration. Several studies have examined the stress response in critically ill dogs and demonstrated that an exaggerated basal cortisol concentration was negatively associated with survival [1416]. Further, the normal physiological response mounted by some patients may be insufficient for the degree of illness, and the adrenal gland may be unable to meet the demands of ongoing stress [17].…”
Section: Discussionmentioning
confidence: 99%